STRATEGI IMPLEMENTASI KEBIJAKAN PEMBELAJARAN TEMATIK TERPADU KURIKULUM 2013 (Studi Kasus MA Pembangunan Lamongan) - Husen Husen; Abid Muhtarom (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2018)
Learning activity is very important thing in education system. The approach uses 2013 curriculum in MA Pembangunan Lamongan. The main purpose of this research is to describe and analyze the implementation of 2013 curriculum integrated with thematic learning policy at MA Pembangunan Lamongan. The research used in this study is qualitative descriptive approach  with a statistical data model using analysis software Eviews 9. And the data in this study is the results of questionnaires and interviews with respondents and observation of learning implementation. The subject of this study is the leader of the MA Pembangunan Lamongan school, the vice leader of the curriculum and the teachers of the MA Pembangunan Lamongan.  Based on the results of the research that the implementation of 2013 curriculum strategy integrated with thematic learning in the MA Pembangunan Lamongan has been categorized as good, it can be seen from the aspects of mastery, understanding and ability of teachers in the learning planning process, implementation of learning, and assessment of learning outcomes as well as the supervision process carried out by the head of the school has run optimally in accordance with the duties and responsibilities as stated in the Republic of Indonesia Minister of Education and Culture (Permendikbud) Regulation Number 65 of 2013 concerning the Basic and Middle Education Process Standards.Keywords: Thematic learning policy, 2013 curriculum